DEMOGRAPHIC AND SOCIAL TRENDS IN THE RUSSIAN ARCTIC - Pavel M. Dashkevich; Natalia A. Flud; Irina I. Eliseeva (Север и рынок: формирование экономического порядка)
The implementation of national policy in the Arctic plays a multifaceted role in ensuring national security and sovereignty across diverse domains, including resource management, transportation, environmental protection, military strategy, and others. Addressing these strategic objectives necessitates a focus on preserving and building up the human capital of the northern regions, with particular emphasis on demographic trends and labor potential development. This study aims to evaluate the extent and dynamics of depopulation in the Russian Arctic, examining its causes and implications for the labor market both across the entire Russian Arctic and within specific regions that are wholly or partially included in it. The relevance of this research stems from the pressing challenge posed by population and workforce decline, which represents a significant threat to the successful implementation of the Arctic Development Strategy through 2035. The negative demographic trends observed in the region are primarily driven by unresolved socio-economic issues, a declining standard of living among Arctic residents, and the depreciation of northern benefits. The practical significance of this study lies in its potential to inform the development and prioritization of public policy measures aimed at addressing these challenges, with a focus on the unique characteristics of individual Arctic regions. Key measures to stabilize and grow the population in the Arctic include comprehensive support for families with children, poverty reduction initiatives, retention of local youth and attraction of young professionals from other regions, economic diversification, and the establishment of competitive services to meet residents’ needs in healthcare, general and vocational education, infrastructure, and other essential aspects of quality of life in northern latitudes.